2019
DOI: 10.1002/pola.29345
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of poly(lactide) with N‐phenyl maleimide using N‐acetoxy‐phthalimide during reactive extrusion

Abstract: Radical grafting of poly(lactide) (PLA) during postpolymerization reactive extrusion is usually done with peroxide initiation, leading to undesirable side reactions (branching or crosslinking) and to difficulties to control the process parameters as well as the final macromolecular structure. The use of N‐acetoxy‐phthalimide (NAPI) was investigated as an alternative to peroxides for the functionalization in the melt of PLA with N‐phenylmaleimide (PhM) monomer. The use of NAPI was found to lead to similar graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Passaglia and co-workers demonstrated that additives with faster relative rates of radical chain transfer compared to MA can improve the reaction outcome . Rolere et al explored N -acetoxy-phthalimide radicals as HAT reagents complementary to peroxides, but minimal functionalization was observed under harsh reaction conditions (200 °C). , In an example of polar functionalization, Ponsart et al used lithium diisopropyl amide to generate an ester enolate on poly­(caprolactone) (PCL), which was subsequently reacted with a variety of electrophiles. PCL with up to 10 mol % functional group incorporation was achieved, but the harsh conditions employed caused polymer degradation and limited the scope of accessible transformations (Figure C, bottom).…”
Section: Introductionmentioning
confidence: 99%
“…Passaglia and co-workers demonstrated that additives with faster relative rates of radical chain transfer compared to MA can improve the reaction outcome . Rolere et al explored N -acetoxy-phthalimide radicals as HAT reagents complementary to peroxides, but minimal functionalization was observed under harsh reaction conditions (200 °C). , In an example of polar functionalization, Ponsart et al used lithium diisopropyl amide to generate an ester enolate on poly­(caprolactone) (PCL), which was subsequently reacted with a variety of electrophiles. PCL with up to 10 mol % functional group incorporation was achieved, but the harsh conditions employed caused polymer degradation and limited the scope of accessible transformations (Figure C, bottom).…”
Section: Introductionmentioning
confidence: 99%